2004
DOI: 10.1128/aem.70.2.1190-1198.2004
|View full text |Cite
|
Sign up to set email alerts
|

Two Bacteria Phylotypes Are Predominant in the Suiyo Seamount Hydrothermal Plume

Abstract: Microbial diversity and populations in a hydrothermal plume that was present inside the caldera of the Suiyo Seamount, a submarine volcano on the Izu-Bonin Arc, were investigated by performing a phylogenetic analysis of the 16S rRNA gene and by using fluorescence in situ hybridization (FISH). Corresponding to transmissivity, an indicator of turbidity, the vertical total cell count as determined by 4,6-diamidino-2-phenylindole (DAPI) staining varied from 5.6 ؋ 10 4 to 1.1 ؋ 10 5 cells ml ؊1 , and the apparent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(155 citation statements)
references
References 49 publications
3
152
0
Order By: Relevance
“…The Epsilonproteobacteria have been known as common member discovered from benthic mixing zone of hydrothermal system (Campbell et al 2006), and a majority of epibiotic microbial community on Sinkaia crosnieri Watsuji et al 2010). The free-living Gammaproteobacteria, SUP05 potential sulfur oxidizing phylotype, dwelled in hydrothermal system have been discovered as common member in chemoautotrophic group of hydrothermal plume (Dick et al 2013;Sunamura et al 2004). The different ecophysiological functions between Epsilonproteobacteria and Gammaproteobacteria probably induced the habitat segregation within hydrothermal system (Nakagawa and Takai 2008;Yamamoto and Takai 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The Epsilonproteobacteria have been known as common member discovered from benthic mixing zone of hydrothermal system (Campbell et al 2006), and a majority of epibiotic microbial community on Sinkaia crosnieri Watsuji et al 2010). The free-living Gammaproteobacteria, SUP05 potential sulfur oxidizing phylotype, dwelled in hydrothermal system have been discovered as common member in chemoautotrophic group of hydrothermal plume (Dick et al 2013;Sunamura et al 2004). The different ecophysiological functions between Epsilonproteobacteria and Gammaproteobacteria probably induced the habitat segregation within hydrothermal system (Nakagawa and Takai 2008;Yamamoto and Takai 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, little is known about the nature of plume microbial communities or their relationship to those of the seafloor or surrounding deep seawater. Several studies have reported the SUP05 group of sulfur-oxidizing Gammaproteobacteria in deep-sea hydrothermal plumes in widespread geographical locations (Sunamura et al, 2004;Dick and Tebo, 2010;German et al, 2010). Other prevalent microbial groups identified in plumes include Epsilonproteobacteria (Sunamura et al, 2004;Nakagawa et al, 2005;German et al, 2010), ammonia-oxidizing Betaproteobacteria (Lam et al, 2008), methanotrophs (Naganuma et al, 2004;Lam et al, 2008) and Marine Group I (MGI) archaea (Takai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the samples from the MOT, most oligonucleotide probes identified very few cells, with the exception of SUP05-187. The SUP05 group of sulfur oxidizers in Gammaproteobacteria was most abundant near vent fauna habitats in the MOT, as previously shown in the hydrothermal plume at the Suiyo Seamount (Sunamura et al 2004). Sulfur oxidation would be one of the most feasible reactions in the hydrothermal environment of the MOT.…”
Section: Quantitative Assessment Of Microbial Community Composition Bmentioning
confidence: 56%